Examining the effects of physical activity on the impact of older people’s bereavement in ELSA data - Zsuzsanna; Carol; David; Jasper (Magyar Gerontológia, 2025)
The loss of a loved one and consequent bereavement and grief have a negative impact on physical and mental health and can cause high stress levels.